2014
DOI: 10.9790/3008-09615461
|View full text |Cite
|
Sign up to set email alerts
|

Tobramycin-Silver Nanocomposite: A New Trend of Antimicrobials against Resistant Strains

Abstract: Effectiveness of many antibiotics has been remarkably decreased due to bacterial resistance. the present work aims to explore a novel antimicrobial nanocomposite with greater efficacy against resistant bacteria. Tobramycin-silver nanocomposite was synthesized and characterized by Transmission Electron Microscopy, UV-VIS Spectroscopy, Zetasizer and Fourier Transform Infrared spectroscopy. Antimicrobial activity of tobramycin, silver nanoparticles and Tobramycin-silver nanocomposite was tested against Staphyloco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Accordingly, Helal et al . () demonstrated tobramycin‐silver nanocomposite as a novel antimicrobial agent. They studied the antimicrobial activity against different antibiotic resistant micro‐organisms such as Staph.…”
Section: Role Of Various Nanomaterials For the Management Of Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, Helal et al . () demonstrated tobramycin‐silver nanocomposite as a novel antimicrobial agent. They studied the antimicrobial activity against different antibiotic resistant micro‐organisms such as Staph.…”
Section: Role Of Various Nanomaterials For the Management Of Infectionsmentioning
confidence: 99%
“…aeruginosa (MTCC 424) and Salmonella enterica (MTCC 1253) (Potara et al 2011;Kaur and Thakur 2013). Accordingly, Helal et al (2014) demonstrated tobramycin-silver nanocomposite as a novel antimicrobial agent. They studied the antimicrobial activity against different antibiotic resistant micro-organisms such as Staph.…”
Section: Nanocompositesmentioning
confidence: 99%